Influence of Blood Insulin Levels on The Daily Life and Health of Patients with COPD - Fattakhov Rafkat Akramovich (Zien Journals, 2024)
The study examines hyperinsulinemia in patients with COPD and its impact on their lives. Clinical data and biochemical indicators were analyzed, including blood insulin levels and CAT questionnaire outcomes. A high frequency of hyperinsulinemia was identified, which has clinical significance for treatment and improving prognosis and quality of life for patients.
Keywords: COPD; Chronic obstructive pulmonary disease; metabolic syndrome